Range Extension of Mesophotic Kelps (Ochrophyta: Laminariales and Tilopteridales) in the Central North Atlantic: Opportunities for Marine Forest Research and Conservation. Issue 4 (22nd April 2021) - Tempera, Fernando; Milla‐Figueras, David; Sinde‐Mano, Ana Luísa; Atchoi, Elizabeth; Afonso, Pedro
Abstract : Kelp was first recorded for the remote warm‐temperate Azores archipelago (central North Atlantic) in 1971, when a few Laminaria specimens were collected on the Formigas Bank at depths beyond conventional SCUBA diving reach. A shortage of technical means and projects targeting mesophotic environments has since kept this offshore marine protected area as the single known kelp occurrence site. Here, we present new kelp records collected on previously unexplored mesophotic reefs using remote imaging systems, open‐ and closed‐circuit SCUBA diving, and fisheries bycatch information. The new data extend the known distribution range of kelp in the Azores 350 km to the west and 25 km to the southwest, henceforth including several island shelves in the eastern and central Azores. In addition to the previously recorded Laminaria ochroleuca, kelp specimens with a morphology akin to Phyllariopsis brevipes subsp. brevipes are also reported. For the first time, seabed imagery is used to document the depth‐wise diversity of the Azores kelp beds and their associated biota. Our findings emphasize the poor knowledge that persists in regard to Macaronesia's mesophotic environments located beyond conventional SCUBA diving limits. The new on‐shelf kelp occurrences add conservation value to coastal areas and should facilitate island‐based research. However, their greater proximity to land‐based impacts and exposure to climate change also raise management needs.